Terapeuci – żydowscy prekursorzy monastycyzmu chrześcijańskiego w De vita contemplativa Filona z Aleksandrii - Leszek Misiarczyk (Vox Patrum, 2018)
The article analyzes the most important aspects of the life of therapists, the Jewish precursors of Christian monasticism. The author advocates the datation of the De vita contemplativa for the years 40-41 of the first century and presents arguments for the authorship of Philo. Then he emphasizes the apologetic nature of the text and its content. The author is in favor of the hypothesis that therapists were not essenes, but a separate group of ascetics in Judaism of the 1st century AD. He is not convinced by the hypothesis that the Philo’s treaty is a literary fiction and the presentation of an ideal community. Too many details in the text contradict this opinion and even indicate that Philo himself knew the life of therapists from autopsy. Direct influence of therapists on Christian monastic life is impossible to demonstrate, while indirect influence manifests itself in the following elements poor clothing, modest meals: bread, salt and water, devoting little attention to the needs of the body - only as much as necessary for life, getting rid of ownership by giving it to the closest relatives, praying at sunrise, praying with hands raised to heaven, practicing allegorical exegesis of the Old Testament, living in continence. In the case of cenobites: common life under the direction of the superior, shared meals, common prayers, houses divided into a residential part and a monastery as a place of prayer.